Evaluating implementation of the World Health Organization’s Strategic Approach to strengthening sexual and reproductive health policies and programs to address unintended pregnancy and unsafe abortion - Rashid, Shusmita (Reprod Health, 2017)
BACKGROUND: We conducted a process evaluation to assess how the World Health Organization’s (WHO) Strategic Approach to strengthening sexual and reproductive health policies and programs (“the SA”) was used in 15 countries that requested WHO’s technical support in addressing unintended pregnancy and unsafe abortion. The SA is a three-stage planning, policy, and program implementation process. We used the social ecological model (SEM) to analyze the contextual factors that influenced SA implementation. METHODS: We used a two-phased sequential approach to data collection and analysis. In Phase A, we conducted a document and literature review and synthesized data thematically. In Phase B, we conducted interviews with stakeholders who used the SA in the countries of interest. We used a qualitative method triangulation technique to analyze and combine data from both phases to understand how the SA was implemented in each country. RESULTS: Data from 145 documents and 19 interviews described the SA process and activities in each country. All 15 countries completed Stage 1 activities. The activities of Stage 1 determined activities in subsequent stages and varied across countries. Following Stage 1, some countries focused on reforming policies to improve access to sexual and reproductive health (SRH) services whereas others focused on improving provider-level capacity to enhance SRH service quality and improving community-level SRH education. We identified factors across SEM levels that affected SA implementation, including individual- and community-level perceptions of using the SA and the recommendations that emerged from its use, organizational capacity to conduct SA activities, and how well these activities aligned with the existing political climate. Stakeholders perceived SA implementation to be country-driven and systematic in bringing attention to important SRH issues in their countries. CONCLUSION: We identified key success factors for influencing the individual, organization, and system change required for implementing the SA. These include sustaining stakeholder engagement for all SA stages, monitoring and reporting on activities, and leveraging activities and outputs from each SA stage to obtain technical and financial support for subsequent stages. Results may be used to optimize ongoing implementation efforts to improve access to and the quality of SRH services. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12978-017-0405-3) contains supplementary material, which is available to authorized users.